2017
DOI: 10.3390/ijms18040746
|View full text |Cite
|
Sign up to set email alerts
|

TRPV4 Stimulation Induced Melatonin Secretion by Increasing Arylalkymine N-acetyltransferase (AANAT) Protein Level

Abstract: Melatonin is a molecule which has gained a great deal of interest in many areas of science; its synthesis was classically known to be in the pineal gland. However, many organs synthesize melatonin, such as several ocular structures. Melatonin is known to participate in many functions apart from its main action regulating the circadian rhythm. It is synthesized from serotonin in two steps, with a rate-limiting step carried out by arylalkymine N-acetyltransferase (AANAT). In this report, the role of TRPV4 channe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 37 publications
0
5
0
Order By: Relevance
“…these cells are able to produce the indolamine (Fig. 6) (Alkozi et al, 2017c). A small interference siRNA approach confirmed that all those effects are mediated by TRPV4 (Alkozi et al, 2017b).…”
Section: Melatonin: a Relevant Player In Iop Regulationmentioning
confidence: 63%
See 1 more Smart Citation
“…these cells are able to produce the indolamine (Fig. 6) (Alkozi et al, 2017c). A small interference siRNA approach confirmed that all those effects are mediated by TRPV4 (Alkozi et al, 2017b).…”
Section: Melatonin: a Relevant Player In Iop Regulationmentioning
confidence: 63%
“…Values represent the mean ± SEM (n = 6; *p < 0.05, **p < 0.01, ***p < 0.001 versus time 0). Taken from (Alkozi et al, 2017c(Alkozi et al, : open access). 1928).…”
Section: Melatonin: a Relevant Player In Iop Regulationmentioning
confidence: 99%
“…Likewise, darkness increases AANAT expression and melatonin production in lens epithelial cells. 67 Lenses are transparent tissues inside the eyes used for focusing light. 68 Oxidative stress and inflammatory responses affect lens clarity and function.…”
Section: The Presence and Role Of Melatonin In The Structure Of The Eyementioning
confidence: 99%
“…We wondered whether intraocular hypertension correlated with the altered expression of dopamine and melatonin heteroreceptor complexes. First of all, we took advantage of an in vitro model of hypertension, described in Reference [54], consisting of the activation of the transient Interestingly, and as previously described by Alkozi et al, [34], none of the melatonin receptor agonists, melatonin or IIK7, were able to decrease cAMP levels in these cells. Next, we analyzed ERK1/2 phosphorylation, which was significantly enhanced when 7-OH-PIPAT was added ( Figure 4B,E).…”
Section: Differential Expression Of D3-mt1 and D3-mt2 Heteroreceptor mentioning
confidence: 99%
“…We wondered whether intraocular hypertension correlated with the altered expression of dopamine and melatonin heteroreceptor complexes. First of all, we took advantage of an in vitro model of hypertension, described in Reference [54], consisting of the activation of the transient receptor potential vanilloid 4 (TRPV4) channel. Such activation in 59HCE cells using GSK1016790A mimics the ion fluxes that drive the increase in hydrostatic pressure that occurs in the hypertensive/glaucomatous eye.…”
Section: Differential Expression Of D 3 -Mt 1 and D 3 -Mt 2 Heterorecmentioning
confidence: 99%